Changes of the in vivo kinematics of the human medial longitudinal foot arch, first metatarsophalangeal joint, and the length of plantar fascia in different running patterns - Sun, Xiaole; Su, Wanyan; Zhang, Faning; Ye, Dongqiang; Wang, Shaobai; Zhang, Shen; Fu, Weijie (Frontiers in Bioengineering and Biotechnology, 2022)
This study aimed to explore the acute effects of foot strike patterns on the six degrees of freedom (6DOF) kinematics of the medial longitudinal arch (MLA) and first metatarsophalangeal joint (MTPJ), and the length of the plantar fascia (PF) during the stance phase of running. Fifteen healthy male runners who all ran with a regular rearfoot strike (RFS) pattern were required to run with forefoot strike (FFS) and RFS patterns. A high-speed dual fluoroscopic imaging system (100 Hz) and 3D force platform (2000 Hz) were used to acquire X-ray images of the foot bones and ground reaction force data during the stance phase of running (3 m/s  5%) simultaneously. Then, 3D bone models and coordinate system built from the computed tomography image of the calcaneus, first metatarsal, and phalanges combined with 3D-2D registration were used to obtain the 6DOF data of the MLA and first MTPJ and the length of the PF. Compared with RFS, in FFS, 1) the range of motion (ROM) of medial/lateral, anterior/posterior, plantarflexion/dorsiflexion, and adduction/abduction motions of the MLA were increased significantly; 2) the ROM of anterior/posterior, superior/inferior, and extension/flexion motions of the first MTPJ were increased significantly; 3) the maximum strain, maximum length, and power of the PF increased significantly. Running with FFS may increase the energy storage and release of the MLA and PF, as well as the push-off effect of the MTPJ. Meanwhile, FFS enhances the mechanical properties of the PF and the cushioning capacity of the MLA potentially. Moreover, the MLA deformation and the first MTPJ extended angle would lengthen the PF.